2022
DOI: 10.1021/acs.iecr.2c02111
|View full text |Cite
|
Sign up to set email alerts
|

Automated versus Chemically Intuitive Deconvolution of Density Functional Theory (DFT)-Based Gas-Phase Errors in Nitrogen Compounds

Abstract: Catalysis models involving metal surfaces and gases are regularly based on density functional theory (DFT) calculations at the generalized gradient approximation (GGA). Such models may have large errors in view of the poor DFT-GGA description of gas-phase molecules with multiple bonds. Here, we analyze three correction schemes for the PBE-calculated Gibbs energies of formation of 13 nitrogen compounds. The first scheme is sequential and based on chemical intuition, the second one is an automated optimization b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The total error in the DFT-calculated free energy of formation of , denoted , is determined as the difference between the DFT prediction ( ) and the experimental value as shown in Eq. 12 : 36 , 38 40 , 44 , 45 , 53 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total error in the DFT-calculated free energy of formation of , denoted , is determined as the difference between the DFT prediction ( ) and the experimental value as shown in Eq. 12 : 36 , 38 40 , 44 , 45 , 53 …”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, previous works have shown that when GGA, meta-GGA, and/or hybrid functionals are used to model various families of C- 40 , 43 and N-containing compounds 38 , 39 , 53 , H 2 O 2(g) and O 2(g) 36 , 44 , 45 , sizable gas-phase errors are still found. Such errors are systematic and can be mitigated by means of inexpensive semiempirical corrections 38 , 40 , 41 , 43 , 53 . This strongly suggests that a cautious and early assessment of gas-phase errors is needed to guarantee the accuracy of (electro)catalytic models based upon DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…For a reaction in the gas phase, the enthalpy (Δ r H DFT ) and Gibbs energy (Δ r G DFT ) change can be estimated from DFT calculations using the following equations:Δ r G DFT = Δ r H DFT − T Δ S In eqn (1), Δ E DFT is the sum of the DFT energies of the products multiplied by their respective stoichiometric coefficients minus the DFT energies of the reactants also multiplied by their respective stoichiometric coefficients. Analogously, ΔZPE is the change in the zero-point energies of products and reactants calculated through the harmonic oscillator approximation, and is the change in the heat capacity contribution, which is usually neglected because of the cancellation of the contributions of products and reactants in the range of 0 to 298.15 K. 6,28,35 However, we anticipate that this term may not be negligible for reactions with numerous proton–electron transfers. In eqn (2), T Δ S represents the difference between the total entropies of the products and reactants, usually taken from thermodynamic tables.…”
Section: Detection and Quantification Of Dft Gas-phase Errorsmentioning
confidence: 99%
“…This semiempirical energy can then be used to calculate the equilibrium potential of nitrate reduction reactions. Given that the error in the DFT-calculated free energy of HNO 3 is larger than 1 eV for several GGA and meta-GGA xc-functionals, 25,28,29,51 overlooking it leads to seriously impaired reaction energies and equilibrium potentials, especially for reactions with small number of transferred electrons.…”
mentioning
confidence: 99%
“…The Gibbs free energy difference for the considered elementary steps (Δ G ) was approximated as Δ G ≈ Δ E DFT + ΔZPE – T Δ S + Δ E solvation , where Δ E DFT is the PBE-calculated energy difference, ΔZPE is the zero-point energy change, and T Δ S is the corresponding entropy change at 298.15 K. For gas-phase molecules the total entropies were obtained from thermodynamic tables, and their free energies were corrected semiempirically (more details on this procedure are available in section S1), while for adsorbates Δ S only includes vibrational entropies. Δ E solvation is the contribution of solvent-adsorbate interactions to the free energy, which we evaluated using four different solvation approaches, see sections S1 and S2.…”
Section: Computational Detailsmentioning
confidence: 99%